2021
DOI: 10.3390/genes12091451
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Cowpea [Vigna unguiculata (L.) Walp.] Germplasm Collected from Togo Based on DArT Markers

Abstract: Crop genetic diversity is a sine qua non for continuous progress in the development of improved varieties, hence the need for germplasm collection, conservation and characterization. Over the years, cowpea has contributed immensely to the nutrition and economic life of the people in Togo. However, the bulk of varieties grown by farmers are landraces due to the absence of any serious genetic improvement activity on cowpea in the country. In this study, the genetic diversity and population structure of 255 cowpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Results of AMOVA further revealed higher variation within the genetic populations than between the populations. A recent study using 255 cowpea accessions collected from six regions in Togo reported significant genetic variations among and within populations, with variations among individuals that were within each of the six geographic origins explaining the highest percentage (78%) of total variability (Gbedevi et al, 2021). Similar studies have been reported by several authors.…”
Section: Detection Of Genetic Relatednesssupporting
confidence: 82%
See 2 more Smart Citations
“…Results of AMOVA further revealed higher variation within the genetic populations than between the populations. A recent study using 255 cowpea accessions collected from six regions in Togo reported significant genetic variations among and within populations, with variations among individuals that were within each of the six geographic origins explaining the highest percentage (78%) of total variability (Gbedevi et al, 2021). Similar studies have been reported by several authors.…”
Section: Detection Of Genetic Relatednesssupporting
confidence: 82%
“…This marker density and distribution is modest for dissection of molecular diversity, genetic relatedness, population structure, linkage disequilibrium, genomic selection and even a medium resolution QTL discovery. Marker density of less than 5,000 SNPs that are well distributed across the genome have been deployed successfully to decipher genetic diversity and other molecular and genetic applications in crops (Akohoue et al, 2020;Chander et al, 2021;Gbedevi et al, 2021).…”
Section: Informativeness Of the Marker Panelmentioning
confidence: 99%
See 1 more Smart Citation
“…(2017), but whether or not autogamy predominates over allogamy has yet to be clarified. The high inbreeding coefficient also indicates that accessions investigated are near the inbred line state (Gbedevi et al., 2021), an insight that provides impetus to quickly advance breeding population development for agronomic and functional traits of importance in the species. Based on their relatively high expected heterozygosity and mean allelic richness values, the Volta population in particular, and the Eastern and Oueme populations to some extent, stand out as promising sources of genetic material for both breeding and conservation programs.…”
Section: Discussionmentioning
confidence: 99%
“…This technology, based on microarray hybridizations, can detect DNA variation, and the presence versus absence of individual fragments, without the need for sequence information. DArT analysis was already applied to the germplasm characterization of barley [ 20 ], strawberry [ 21 ], macadamia [ 22 ] and, to our knowledge, very recently to cowpea from Ethiopia [ 23 ] and Togo [ 24 ].…”
Section: Introductionmentioning
confidence: 99%